Corrosion and scale inhibitor and preparation method thereof

CN122325016BActive Publication Date: 2026-10-23HUBEI QILANG NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610771468.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-10-23
Estimated Expiration
2046-06-01

AI Technical Summary

Technical Problem

有机膦酸含有磷,对环境存在较大的危害;而硫酸锌除会导致重金属沉积外,对水体和环境微生物存在较大毒性,会破坏水体生态环境,严重影响水质

Benefits of technology

1. 本申请以棕榈油酸-丙烯酸-木质素磺酸共聚物为主要组分,辅以马来酸-丙烯酸-EDTA共聚物阻垢剂,采用特定配比,复配了缓蚀阻垢剂;本申请的缓蚀阻垢剂中不含磷和硫酸锌,也不含任何对环境危害大的组分,主要组分的原料以天然物质为主,环保型较佳。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an inhibitor and scale inhibitor and a preparation method thereof. In one aspect, the application provides an inhibitor and scale inhibitor, and the mass ratio of components of the inhibitor and scale inhibitor comprises the following: 60-70 parts of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer, and 30-40 parts of maleic acid-acrylic acid-EDTA copolymer. In another aspect, the application provides a preparation method of the inhibitor and scale inhibitor, and the preparation method comprises the following steps: S1, preparing palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer; S2, preparing maleic acid-acrylic acid-EDTA copolymer; and S3, weighing each component according to the formula amount, and preparing the inhibitor and scale inhibitor after sufficient mixing. The application has better environmental protection, better scale inhibition effect on calcium ions and magnesium ions, better dispersibility, and excellent corrosion inhibition effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coal gasification ash water treatment technology, and in particular to a corrosion and scale inhibitor and its preparation method. Background Technology

[0002] Coal gasification has gradually become an important technology for the comprehensive development and utilization of coal in my country, and is also a clean coal resource utilization technology that my country is vigorously developing. Coal gasification is a chemical technology that converts coal into combustible gases containing carbon monoxide and hydrogen through high-temperature reactions. It can produce syngas, industrial fuel gas, and other products, which are applied in power generation, ammonia synthesis, and methanol production. However, coal gasification consumes a large amount of cooling water; therefore, improving the reuse rate of circulating cooling water is crucial for water conservation and energy saving. In coal gasification, as the concentration ratio of circulating cooling water increases, some slightly soluble substances in the water, such as calcium carbonate and calcium phosphate, easily form scale on heat exchange surfaces, seriously affecting the normal operation of the circulating cooling water system. Scale formation also leads to differences in oxygen and salt ion concentrations and temperature on metal surfaces, resulting in a concentration cell effect that accelerates pipeline corrosion. Currently, the most effective solution to these problems using existing technology is to add corrosion and scale inhibitors.

[0003] Existing corrosion and scale inhibitors are typically formulated by combining scale inhibitors and corrosion inhibitors. For example, corrosion and scale inhibitors are often obtained by combining phosphonic acid, carboxylic acid, and / or sulfonic acid scale inhibitors with zinc sulfate corrosion inhibitors; another example is corrosion and scale inhibitors obtained by combining copolymer scale inhibitors with zinc sulfate and low-phosphorus corrosion inhibitors. These are commonly used. With increasingly stringent environmental protection requirements in my country, the environmental hazards posed by corrosion and scale inhibitors containing phosphorus, heavy metals, and / or harmful polymers are receiving growing attention. Among commonly used corrosion and scale inhibitors, those containing organophosphonic acids and zinc sulfate pose significant environmental risks. Organophosphonic acids contain phosphorus, which is highly harmful to the environment; while zinc sulfate, in addition to causing heavy metal deposition, is highly toxic to aquatic bodies and environmental microorganisms, damaging the aquatic ecosystem and severely impacting water quality.

[0004] Therefore, providing a green and environmentally friendly corrosion and scale inhibitor is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] In order to solve at least one of the above-mentioned technical problems, and to develop a corrosion and scale inhibitor that is more environmentally friendly, has a better scale inhibition effect on calcium and magnesium ions, better dispersibility, and has a better corrosion inhibition effect, this application provides a corrosion and scale inhibitor and its preparation method.

[0006] On the one hand, this application provides a corrosion and scale inhibitor, wherein the mass ratio of each component of the corrosion and scale inhibitor includes: 60-70 parts of palm oleic acid-acrylic acid-lignin sulfonic acid copolymer and 30-40 parts of maleic acid-acrylic acid-EDTA copolymer.

[0007] Optionally, the preparation of the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer includes the following steps: S1-1. Weigh palmitate, acrylic acid and lignin sulfonate precisely according to the mass ratio of 0.4~0.6:3.5~4:1. Prepare a 30~35% mass fraction solution of lignin sulfonate with water. Add palmitate, hydrogen peroxide and initiator. Heat to 70~75℃ and stir under nitrogen protection for 20~30 min to obtain the reaction solution. S1-2. Add acrylic acid to the reaction solution, then adjust the pH value to 2.5-3 with hydrochloric acid, and continue to stir the reaction under nitrogen protection for more than 12 hours to obtain the reaction mixture. S1-3. Cool the reaction mixture to room temperature, centrifuge to remove the aqueous phase, wash the product with acetone, and then dry it to obtain the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer.

[0008] Further optionally, in step S1-1, the mass ratio of palmitate, acrylic acid and lignin sulfonate is 0.48~0.5:3.8:1.

[0009] Optionally, in step S1-1, the hydrogen peroxide is selected from a product with a mass fraction of 20%, and the amount of hydrogen peroxide added accounts for 80-85% of the total mass of lignin sulfonate.

[0010] Optionally, in step S1-1, potassium persulfate is selected as the initiator, and the amount of initiator added accounts for 2 to 2.5% of the total mass of lignin sulfonate.

[0011] Optionally, the preparation of the maleic acid-acrylic acid-EDTA copolymer includes the following steps: S2-1. Weigh maleic anhydride, acrylic acid and EDTA in a molar ratio of 1:1.4~1.6:0.4~0.6, add water to prepare a solution, add initiator, react at 80~85℃ for more than 5.5h, cool and add sodium hydroxide to adjust the pH to 5.8~6, filter out the product; S2-2. The product is washed with deionized water and then dried to obtain maleic acid-acrylic acid-EDTA copolymer.

[0012] Optionally, in step S2-1, the molar ratio of maleic anhydride, acrylic acid, and EDTA is 1:1.45:0.5.

[0013] Optionally, in step S2-1, the amount of water added is 1.4 to 1.6 times the total mass of maleic anhydride, acrylic acid, and EDTA.

[0014] Optionally, in step S2-1, the initiator is ammonium persulfate, and the amount of initiator added is 0.8-1% of the total mass of maleic anhydride, acrylic acid and EDTA.

[0015] On the other hand, this application provides a method for preparing the above-mentioned corrosion and scale inhibitor, comprising the following steps: S1. Preparation of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer; S2. Preparation of maleic acid-acrylic acid-EDTA copolymer; S3. Weigh each component according to the formula, mix them thoroughly, and then prepare the corrosion and scale inhibitor.

[0016] In summary, the present invention has at least one of the following beneficial technical effects: 1. This application uses palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer as the main component, supplemented with maleic acid-acrylic acid-EDTA copolymer scale inhibitor, and uses a specific ratio to compound a corrosion and scale inhibitor; the corrosion and scale inhibitor of this application does not contain phosphorus and zinc sulfate, nor does it contain any components that are highly harmful to the environment. The raw materials of the main components are mainly natural substances, which is more environmentally friendly.

[0017] 2. Both copolymers in this application exhibit superior high-temperature stability. The compounded corrosion and scale inhibitors demonstrate excellent scale inhibition effects against calcium and magnesium ions, relatively good dispersibility, and superior corrosion inhibition effects on steel, resulting in superior overall performance. Detailed Implementation

[0018] The present application will be further described in detail below with reference to the embodiments.

[0019] This application provides a corrosion and scale inhibitor, wherein the mass ratio of each component of the corrosion and scale inhibitor includes: 60-70 parts of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer and 30-40 parts of maleic acid-acrylic acid-EDTA copolymer.

[0020] The preparation method of the above-mentioned corrosion and scale inhibitor includes the following steps: S1. Preparation of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer; S2. Preparation of maleic acid-acrylic acid-EDTA copolymer; S3. Weigh each component according to the formula, mix them thoroughly, and the corrosion and scale inhibitor is obtained.

[0021] In the existing technology, commercially available corrosion and scale inhibitors with good corrosion inhibition effects are usually made of organophosphonic acid scale inhibitors or copolymer scale inhibitors combined with zinc sulfate. These generally contain phosphorus and / or zinc, which is environmentally unfriendly. This is because, in the existing technology, organophosphoric acid and zinc sulfate have extremely excellent corrosion inhibition effects, while other substances are far less effective.

[0022] Based on lignin sulfonic acid, this application designs a palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer through copolymerization, which has excellent corrosion inhibition and scale inhibition effects. When compounded with maleic acid-acrylic acid-EDTA copolymer, not only is the corrosion inhibition effect unaffected, but the scale inhibition effect against calcium and magnesium ions is further significantly improved.

[0023] The following are preparation examples and embodiments of this application.

[0024] The main raw materials used in the embodiments of this application are all commercially available.

[0025] Sodium palmitate was purchased from Shanghai Aladdin; sodium lignosulfonate was purchased from Jinan Luyi Chemical Technology Co., Ltd.; maleic anhydride with a purity of over 99% was purchased from Shanghai Aladdin; acrylic acid with a purity of over 99% was purchased from Shanghai Aladdin; and EDTA with a purity of over 99.5% was purchased from Shanghai Aladdin.

[0026] The following is a preparation example of this application.

[0027] Preparation Example 1 The preparation of the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer in this example includes the following steps: S1-1. Weigh palmitate, acrylic acid and lignin sulfonate precisely according to the mass ratio of 0.4:3.5:1. Prepare a 30% mass solution of lignin sulfonate with water. Add palmitate, 20% hydrogen peroxide (80% of the total mass of lignin sulfonate), and 2% potassium persulfate (2% of the total mass of lignin sulfonate). Heat to 70~75℃ and stir for 20 minutes under nitrogen protection to obtain the reaction solution. S1-2. Add acrylic acid to the reaction solution, then adjust the pH value to 3 with hydrochloric acid, and continue to stir the reaction under nitrogen protection for 12 hours to obtain the reaction mixture. S1-3. Cool the reaction mixture to room temperature, centrifuge to remove the aqueous phase, then wash the product three times with acetone, and vacuum dry at 40°C to constant weight to obtain palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer.

[0028] Preparation Example 2 The preparation of the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer in this example includes the following steps: S1-1. Weigh palmitate, acrylic acid and lignin sulfonate precisely according to a mass ratio of 0.6:4:1. Prepare a 35% mass solution of lignin sulfonate with water. Add palmitate, 20% hydrogen peroxide (85% of the total mass of lignin sulfonate), and 2.5% potassium persulfate (2.5% of the total mass of lignin sulfonate). Heat to 70-75°C and stir under nitrogen protection for 30 minutes to obtain the reaction solution. S1-2. Add acrylic acid to the reaction solution, then adjust the pH value to 2.5 with hydrochloric acid, and continue to stir the reaction under nitrogen protection for 12 hours to obtain the reaction mixture. S1-3. Cool the reaction mixture to room temperature, centrifuge to remove the aqueous phase, then wash the product three times with acetone, and vacuum dry at 40°C to constant weight to obtain palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer.

[0029] Preparation Example 3 The preparation of the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer in this example includes the following steps: S1-1. Weigh palmitate, acrylic acid and lignin sulfonate precisely according to the mass ratio of 0.5:3.8:1. Prepare a 35% mass solution of lignin sulfonate with water. Add palmitate, 20% hydrogen peroxide (85% of the total mass of lignin sulfonate), and 2.2% potassium persulfate (2.2% of the total mass of lignin sulfonate). Heat to 70~75℃ and stir for 25 minutes under nitrogen protection to obtain the reaction solution. S1-2. Add acrylic acid to the reaction solution, then adjust the pH value to 2.5 with hydrochloric acid, and continue to stir the reaction under nitrogen protection for 12 hours to obtain the reaction mixture. S1-3. Cool the reaction mixture to room temperature, centrifuge to remove the aqueous phase, then wash the product three times with acetone, and vacuum dry at 40°C to constant weight to obtain palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer.

[0030] Preparation Example 4 The preparation of the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer in this example includes the following steps: S1-1. Weigh palmitate, acrylic acid and lignin sulfonate precisely according to the mass ratio of 0.48:3.8:1. Prepare a 35% mass solution of lignin sulfonate with water. Add palmitate, 20% hydrogen peroxide (85% of the total mass of lignin sulfonate), and 2.2% potassium persulfate (2.2% of the total mass of lignin sulfonate). Heat to 70~75℃ and stir for 25 minutes under nitrogen protection to obtain the reaction solution. S1-2. Add acrylic acid to the reaction solution, then adjust the pH value to 2.5 with hydrochloric acid, and continue to stir the reaction under nitrogen protection for 12 hours to obtain the reaction mixture. S1-3. Cool the reaction mixture to room temperature, centrifuge to remove the aqueous phase, then wash the product three times with acetone, and vacuum dry at 40°C to constant weight to obtain palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer.

[0031] Preparation Example 5 The preparation of the maleic acid-acrylic acid-EDTA copolymer in this example includes the following steps: S2-1. Weigh maleic anhydride, acrylic acid, and EDTA in a molar ratio of 1:1.4:0.4. Add purified water in an amount equal to 1.4 times the total mass of maleic anhydride, acrylic acid, and EDTA to prepare a solution. Add ammonium persulfate in an amount equal to 0.8% of the total mass of maleic anhydride, acrylic acid, and EDTA. React at 80-85°C for 5.5 hours. After cooling, add sodium hydroxide to adjust the pH to 6 and filter out the product. S2-2. The product was washed three times with deionized water and dried under vacuum at 40°C to constant weight to obtain maleic acid-acrylic acid-EDTA copolymer.

[0032] Preparation Example 6 The preparation of the maleic acid-acrylic acid-EDTA copolymer in this example includes the following steps: S2-1. Weigh maleic anhydride, acrylic acid, and EDTA in a molar ratio of 1:1.6:0.6. Add purified water in an amount equal to 1.6 times the total mass of maleic anhydride, acrylic acid, and EDTA to prepare a solution. Add ammonium persulfate in an amount equal to 1% of the total mass of maleic anhydride, acrylic acid, and EDTA. React at 80-85°C for 5.5 hours. After cooling, add sodium hydroxide to adjust the pH to 5.8 and filter out the product. S2-2. The product was washed three times with deionized water and dried under vacuum at 40°C to constant weight to obtain maleic acid-acrylic acid-EDTA copolymer.

[0033] Preparation Example 7 The preparation of the maleic acid-acrylic acid-EDTA copolymer in this example includes the following steps: S2-1. Weigh maleic anhydride, acrylic acid, and EDTA in a molar ratio of 1:1.45:0.5. Add purified water in an amount equal to 1.5 times the total mass of maleic anhydride, acrylic acid, and EDTA to prepare a solution. Add ammonium persulfate in an amount equal to 1% of the total mass of maleic anhydride, acrylic acid, and EDTA. React at 80-85°C for 6 hours. After cooling, add sodium hydroxide to adjust the pH to 6 and filter out the product. S2-2. The product was washed three times with deionized water and dried under vacuum at 40°C to constant weight to obtain maleic acid-acrylic acid-EDTA copolymer.

[0034] The following are embodiments of this application, all prepared according to the preparation method of this application.

[0035] Example 1 The mass ratio of each component in the phosphorus-free scale inhibitor and dispersant of this embodiment includes: 60 parts of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer and 30 parts of maleic acid-acrylic acid-EDTA copolymer.

[0036] In this embodiment, the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of Preparation Example 1 and the maleic acid-acrylic acid-EDTA copolymer of Preparation Example 5 were selected.

[0037] Example 2 The mass ratio of each component in the phosphorus-free scale inhibitor and dispersant of this embodiment includes: 70 parts of palm oleic acid-acrylic acid-lignin sulfonic acid copolymer and 40 parts of maleic acid-acrylic acid-EDTA copolymer.

[0038] In this embodiment, the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of Preparation Example 1 and the maleic acid-acrylic acid-EDTA copolymer of Preparation Example 5 were selected.

[0039] Example 3 The mass ratio of each component in the phosphorus-free scale inhibitor and dispersant of this embodiment includes: 66 parts of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer and 34 parts of maleic acid-acrylic acid-EDTA copolymer.

[0040] In this embodiment, the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of Preparation Example 1 and the maleic acid-acrylic acid-EDTA copolymer of Preparation Example 5 were selected.

[0041] Example 4 The difference between this embodiment and Example 3 is that this embodiment selects the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of Preparation Example 2 and the maleic acid-acrylic acid-EDTA copolymer of Preparation Example 6.

[0042] Example 5 The difference between this embodiment and Example 3 is that this embodiment selects the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of Example 3 and the maleic acid-acrylic acid-EDTA copolymer of Example 7.

[0043] Example 6 The difference between this embodiment and Example 3 is that this embodiment selects the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of Preparation Example 4 and the maleic acid-acrylic acid-EDTA copolymer of Preparation Example 7.

[0044] Comparative Example 1 This application uses a corrosion and scale inhibitor prepared by compounding Aike AK-610 grey water scale inhibitor and zinc sulfate at a mass ratio of 9.2:0.8 as a comparative example 1.

[0045] Comparative Example 2 The difference between this comparative example and Example 6 is that, in preparing the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer, an equal amount of acrylic acid was used to replace palmitoleate, resulting in the acrylic acid-lignin sulfonic acid copolymer.

[0046] Comparative Example 3 The difference between this comparative example and Example 6 is that the corrosion and scale inhibitor was prepared by compounding maleic acid-acrylic acid-EDTA copolymer and zinc sulfate at a mass ratio of 9:1.

[0047] Comparative Example 4 The difference between this comparative example and Example 6 is that an equal amount of Aike AK-610 grey water scale inhibitor sold by Beijing Sanshida Technology Co., Ltd. was used to replace the maleic acid-acrylic acid-EDTA copolymer.

[0048] The performance of the products from Examples 1-6 and Comparative Examples 1-4 was tested, including their scale inhibition and corrosion inhibition properties.

[0049] The scale inhibition performance was tested using the following methods: The scale inhibitors and dispersants of Examples 1-6 and Comparative Examples 1-4 were all added to the coal gasification process ash water sample liquid (taken from the coal gasification process equipment of a coal chemical plant) at an addition amount of 50 mg / L. Then the coal gasification process ash water sample liquid was heated to 250°C and kept at that temperature for 30 min, and then cooled to room temperature. Use a calcium ion concentration detector and a magnesium ion concentration detector to measure the ion concentration before and after the test. Calculate the scale inhibition rate according to the formula: (previous concentration - subsequent concentration) / previous concentration = scale inhibition rate.

[0050] The corrosion inhibition performance was tested using the rotating plate method described in GB / T 18175-2014.

[0051] The results are shown in Table 1 below.

[0052] Table 1. Performance test results of products from Examples 1-6 and Comparative Examples 1-4 ; As can be seen from the data in Table 1, the corrosion and scale inhibitors of Examples 1-6 of this application exhibit excellent scale inhibition effects on calcium and magnesium ions at a high temperature of 250℃, reaching over 98%, and also have extremely high corrosion inhibition rates, demonstrating excellent corrosion inhibition performance. Comparative Example 1 of the prior art shows relatively good scale inhibition rates for calcium and magnesium ions, approaching 90%, but its corrosion inhibition rate is significantly lower than that of Examples 1-6 of this application. Therefore, the corrosion and scale inhibitors of this application exhibit better stability under high-temperature conditions, superior scale inhibition effects on calcium and magnesium ions compared to existing commercially available scale inhibitors, and excellent corrosion inhibition effects on steel, demonstrating outstanding overall performance.

[0053] The data in Table 1, comparing the data from Examples 1 to 6, shows that the scale inhibition and corrosion inhibition effects can be further improved after optimizing the component ratio and the monomer ratio of the two composite copolymers.

[0054] By comparing the data from Example 6 and Comparative Example 2 in Table 1, it can be seen that the corrosion and scale inhibitor of this application, using a palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer, has excellent corrosion inhibition effect; while the acrylic acid-lignin sulfonic acid copolymer also has a certain corrosion inhibition effect, it is significantly inferior to the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of this application. The addition of palmitoleic acid groups significantly enhances the corrosion resistance of steel in this application.

[0055] A comparison of the data from Example 6 and Comparative Examples 3-4 shows that the selection of the two components in the corrosion and scale inhibitor of this application is crucial. Replacing the maleic acid-acrylic acid-EDTA copolymer with other scale inhibitor components, or replacing the palmitoleic acid-acrylic acid-lignin sulfonate copolymer with zinc sulfate, results in a significant decrease in overall performance when combined with the maleic acid-acrylic acid-EDTA copolymer. Therefore, the palmitoleic acid-acrylic acid-lignin sulfonate copolymer of this application possesses a certain scale inhibition effect, and its scale inhibition effect is excellent when combined with the maleic acid-acrylic acid-EDTA copolymer. However, using other scale inhibitors may lead to functional group interference issues when combined with the palmitoleic acid-acrylic acid-lignin sulfonate copolymer. Furthermore, the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer of this application has a superior corrosion inhibition effect, which is no weaker than that of zinc sulfate. Moreover, the amount used in the formulation of this application is relatively large, which makes the corrosion and scale inhibitor of this application have an excellent corrosion inhibition effect. On the other hand, if zinc sulfate is used as a substitute for compounding, the amount of zinc sulfate added cannot be too high due to the factor that ion interference will affect the scale inhibition effect, and the corrosion inhibition effect is relatively limited.

[0056] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.

Claims

1. A corrosion and scale inhibitor, characterized in that, The mass ratio of each component of the corrosion and scale inhibitor includes: 60-70 parts of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer and 30-40 parts of maleic acid-acrylic acid-EDTA copolymer. The preparation of the palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer includes the following steps: S1-1. Weigh palmitate, acrylic acid and lignin sulfonate precisely according to the mass ratio of 0.4~0.6:3.5~4:

1. Prepare a 30~35% mass fraction solution of lignin sulfonate with water. Add palmitate, hydrogen peroxide and initiator. Heat to 70~75℃ and stir under nitrogen protection for 20~30 min to obtain the reaction solution. S1-2. Add acrylic acid to the reaction solution, then adjust the pH value to 2.5-3 with hydrochloric acid, and continue to stir the reaction under nitrogen protection for more than 12 hours to obtain the reaction mixture. S1-3. Cool the reaction mixture to room temperature, centrifuge to remove the aqueous phase, wash the product with acetone, and then dry it to obtain palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer. The preparation of the maleic acid-acrylic acid-EDTA copolymer includes the following steps: S2-1. Weigh maleic anhydride, acrylic acid and EDTA in a molar ratio of 1:1.4~1.6:0.4~0.6, add water to prepare a solution, add initiator, react at 80~85℃ for more than 5.5h, cool and add sodium hydroxide to adjust the pH to 5.8~6, filter out the product; S2-2. The product is washed with deionized water and then dried to obtain maleic acid-acrylic acid-EDTA copolymer.

2. The corrosion and scale inhibitor according to claim 1, characterized in that, In step S1-1, the mass ratio of palmitate, acrylic acid and lignin sulfonate is 0.48~0.5:3.8:

1.

3. The corrosion and scale inhibitor according to claim 1, characterized in that, In step S1-1, the hydrogen peroxide used is a product with a mass fraction of 20%, and the amount of hydrogen peroxide added accounts for 80-85% of the total mass of lignin sulfonate.

4. The corrosion and scale inhibitor according to claim 1, characterized in that, In step S1-1, potassium persulfate is selected as the initiator, and the amount of initiator added accounts for 2 to 2.5% of the total mass of lignin sulfonate.

5. The corrosion and scale inhibitor according to claim 1, characterized in that, In step S2-1, the molar ratio of maleic anhydride, acrylic acid, and EDTA is 1:1.45:0.

5.

6. The corrosion and scale inhibitor according to claim 1, characterized in that, In step S2-1, the amount of water added is 1.4 to 1.6 times the total mass of maleic anhydride, acrylic acid, and EDTA.

7. The corrosion and scale inhibitor according to claim 1, characterized in that, In step S2-1, ammonium persulfate is selected as the initiator, and the amount of initiator added accounts for 0.8-1% of the total mass of maleic anhydride, acrylic acid and EDTA.

8. A method for preparing the corrosion and scale inhibitor according to claim 1, characterized in that, Includes the following steps: S1. Preparation of palmitoleic acid-acrylic acid-lignin sulfonic acid copolymer; S2. Preparation of maleic acid-acrylic acid-EDTA copolymer; S3. Weigh each component according to the formula, mix them thoroughly, and the corrosion and scale inhibitor is obtained.

Citation Information

Patent Citations

  • Composite coal slurry dispersant used in coal chemical engineering field

    CN105296028A

  • Preparation method of efficient scale inhibitor for circulating cooling water system

    CN111056648A